Acute Calcific Band Keratopathy as an Adverse Effect of Recombinant Human Nerve Growth Factor (Cenegermin): A Multicenter Case Series. Issue 1 (January 2022) - Qureshi, Sana; Ferguson, Tanner J.; Lim, Mira; You, Jae Young; Goshe, Jeffrey M.; Hood, Christopher T.
Abstract : Purpose: Cenegermin, (OXERVATE) a recently Food and Drug Administration-approved topical formulation of recombinant human nerve growth factor, has been used for the treatment of neurotrophic keratopathy (NK). Corneal deposits have been previously reported as a potential adverse effect; however, the clinical characteristics, visual significance, and treatment options have not been fully described. The purpose of this article is to better characterize corneal deposits occurring during treatment with cenegermin for neurotrophic keratopathy. Methods: This was a retrospective, multicenter consecutive case series. Results: We identified 5 patients from 3 institutions who developed a white opacity in varying layers of the cornea, consistent with calcium deposition, during treatment with cenegermin. In all cases, the opacity occurred rapidly over the course of a few weeks after initiation of treatment. Histopathologic examination of the cornea from one corneal patient demonstrated extensive calcification of the stroma extending to 90% depth. Before treatment, all patients had stage 2 or 3 NK (Mackie classification). The deposits were visually significant in all patients and did not resolve after cessation of cenegermin. There were no differences in age, sex, etiology of the NK, corneal transplant status, or concurrent medications between the patients who developed a deposit and 15 other patients with stage 2 or 3 NK who did not. One patient was successfully treated with superficial keratectomy with ethylenediaminetetraacetic acid chelation, one patient underwent penetrating keratoplasty, and one patient received a Boston keratoprosthesis. Conclusions: We report the rapid onset of a corneal opacity after initiation of treatment with cenegermin in patients with stage 2 or 3 NK, consistent with acute calcific band keratopathy. This visually significant adverse finding has not previously been described. We could not identify any risk factors for development. We recommend close monitoring of patients receiving cenegermin therapy because the opacity may be irreversible and may require keratoplasty for visual rehabilitation.